Digital Innovations and Competitive Advantage of Commercial Banks in Kenya - Odhiambo, Juma Wycliffe; Makau, Godfrey (Journal of Business and Strategic Management, 2024)
Purpose: The purpose of the study was to ascertain the role of digital banking technological innovations in enhancing competitive advantage among commercial banks in Kenya. Specifically, the study sought to examine the influence of digital technological innovations for market, digital banking innovations for differentiation, digital innovations for customer satisfaction and the influence of ICT infrastructure on competitive advantage of commercial banks in Kenya Methodology: Descriptive research design was adopted for the present study. The study was carried out in Kenya, covering all the 39 solvent commercial banks in Kenya as of 31st March 2024. The study adopted the census data collection method from the headquarters of the 22 solvent commercial banks belonging to Tier 3. Four key officers including the sales manager, loan officer, relationship manager, and risk manager totaling to 88 were sampled to participate in the study. Findings: The findings indicate that there is a significant relationship between market positioning and competitive advantage (B = 0.292, p = 0.003). On the other hand, Differentiation is established to have a negligible influence on competitive advantage in this model (B = 0.027, p = 0.852). Customer Satisfaction comes out strongly, as a factor that defines competitive advantage (Coefficient = 0.247, P = 0.046). Unique Contribution to Theory, Policy and Practice: The study recommends that Kenyan commercial banks invest in continuous digital innovation, particularly in mobile and Internet banking, to strengthen market positioning, improve brand perception, and offer personalized services. Banks should also enhance their ICT frameworks for better service delivery, data protection, and adaptability to market changes. Emphasizing mobile banking innovations and staying updated with emerging digital trends will help banks reduce customer acquisition costs, expand their customer base, and maintain a competitive edge in a dynamic industry.